2013
DOI: 10.1111/jsap.12146
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective comparison of two peripheral lumbosacral plexus blocks in dogs undergoing pelvic limb orthopaedic surgery

Abstract: Although success rates and perioperative analgesic requirements were not significantly different, the different exposure to anaesthetic agents suggests that the two techniques may not be equivalent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 22 publications
1
22
0
1
Order By: Relevance
“…Although 25% of dogs required methadone in the first 24 postoperative hours, lack of a control group makes it difficult to speculate on a possible sparing effect of hypobaric SA on postoperative analgesic requirements in dogs. Postoperative analgesic requirement was similar to that reported by Campoy et al (2012) in dogs that underwent TPLO and received either extradural morphine -bupivacaine or a femoral and sciatic nerve block, and to that reported in dogs undergoing pelvic limb orthopaedic surgery after performing a lumbosacral plexus block (Vettorato et al 2013). Use of hypobaric SA has previously been reported in a dog that underwent hemipelvectomy (Novello et al 2008), but lateralisation of the block was not discussed probably because of the type of the procedure.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Although 25% of dogs required methadone in the first 24 postoperative hours, lack of a control group makes it difficult to speculate on a possible sparing effect of hypobaric SA on postoperative analgesic requirements in dogs. Postoperative analgesic requirement was similar to that reported by Campoy et al (2012) in dogs that underwent TPLO and received either extradural morphine -bupivacaine or a femoral and sciatic nerve block, and to that reported in dogs undergoing pelvic limb orthopaedic surgery after performing a lumbosacral plexus block (Vettorato et al 2013). Use of hypobaric SA has previously been reported in a dog that underwent hemipelvectomy (Novello et al 2008), but lateralisation of the block was not discussed probably because of the type of the procedure.…”
Section: Resultssupporting
confidence: 79%
“…() in dogs that underwent TPLO and received either extradural morphine – bupivacaine or a femoral and sciatic nerve block, and to that reported in dogs undergoing pelvic limb orthopaedic surgery after performing a lumbosacral plexus block (Vettorato et al . ). Use of hypobaric SA has previously been reported in a dog that underwent hemipelvectomy (Novello et al .…”
Section: Discussionmentioning
confidence: 97%
“…Previous reports have described combining an injection around the ScN with either a proximally-located injection of the lumbar plexus, or a more distally-located injection around either the FN or the SaN in the inguinal region [ 5 8 , 12 , 13 ]. Regardless of the particular technique that is used, the nerve blocks can be used as either the principal anesthetic or, more commonly, as adjuncts to general anesthesia [ 1 4 , 9 , 17 , 20 , 21 ]. If a local anesthetic of sufficient duration is selected, nerve conduction blockade has the potential to provide substantial post-operative pain relief as well [ 1 3 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies reported the anatomical considerations for blocking the two main nerves, the FN and the ScN, at different locations along their courses while subsequent studies described the volume of dye that is required to stain a desired length of target nerve in cadaver specimens and the technical aspects of using ultrasound and/or nerve stimulation to perform these peripheral nerve blocks [ 5 , 6 , 10 , 11 ]. Clinical studies have documented the effects of different FN and ScN blocks on intraoperative analgesia, recovery quality, and the incidence of side effects and complications related to their use for surgical procedures of the pelvic limb [ 1 , 2 , 3 , 4 , 9 , 17 , 20 , 21 ]. Based on these clinical studies in dogs, advantages of using PNBs over neuraxial or opioid-based methods of perioperative pain control include decreased inhaled anesthetic requirements, better maintenance of blood pressure during anesthesia, smoother recoveries from anesthesia, less post-operative urinary retention, and equivalent or superior postoperative analgesia.…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral nerve blocks (PNB) and spinal anaesthesia are techniques that reliably provide effective regional anaesthesia and analgesia during pelvic limb surgical procedures in dogs (Campoy et al 2012;Sarotti et al 2012;Portela et al 2013;Vettorato et al 2013).…”
Section: Introductionmentioning
confidence: 99%